Drug and chemical induced photosensitivity from a clinical perspective. Issue 12 (4th October 2018) - Ibbotson, Sally
Abstract : Drug photosensitivity is a relatively common occurrence and a range of mechanisms may be involved. Abstract : Drug photosensitivity is a relatively common occurrence and a range of mechanisms may be involved. Some of these mechanisms will be discussed, including the most common, that of drug phototoxicity. Different types of photosensitivity are addressed with respect to clinical presentation, mechanisms and additionally the contribution to our understanding through clinically directed investigations and regulatory requirements. Repeated controlled therapeutic use of drug phototoxicity, with psoralen-UVA (PUVA) photochemotherapy and photodynamic therapy (PDT) will also be discussed. Finally, the potential for drug-induced photocarcinogenesis will also be covered.